The Study of Economics: Principles, Concepts & Applications - Mings T. (Turley) (Connecticut: The Dushkin Publishing Group, 1991)
This supplement is designed to aid teachers using Turley Mings's 'The Study of Economics', 4th edition. It contains three resources - Teaching With The Study of Economics, Testing from The Study of Economics, and Transparency Masters to Accompany The Study of Economics - in one manual.
(NP(B/12760, (NP(B/12762s
Keywords: foundations -- microeconomics -- macroeconomics -- world economics